True outcomes for patients on antiretroviral therapy who are "lost to follow-up" in Malawi - Joseph Kwong-Leung Yu; Solomon Chih-Cheng Chen; Kuo-Yang Wang; Chao-Sung Chang; Simon D Makombe; Erik J Schouten; Anthony D Harries (Bulletin of the World Health Organization)
PROBLEM: In many resource-poor countries that are scaling up antiretroviral therapy (ART), 5-25% of patients are reported as "lost to follow-up". This figure is 9% in Malawi. There is no published information about the true outcome status of these patients. APPROACH: In four facilities in northern Malawi, ART registers and master cards were used to identify patients who had not attended the facility for 3 months or more and were thus registered as "lost to follow-up". Clinic staff attempted to trace these patients and ascertain their true outcome status. LOCAL SETTING: Of 253 patients identified as "lost to follow-up", 127 (50%) were dead, 58% of these having died within 3 months of their last clinic visit. Of the 58 patients (23%) found to be alive, 21 were still receiving ART and 37 had stopped treatment (high transport costs being the main reason for 13 patients). Sixty-eight patients (27%) could not be traced, most commonly because of an incorrect address in the register. Fewer patients were alive and more patients could not be traced from the central hospital compared with the peripheral hospitals. RELEVANT CHANGES:Better documentation of patients’ addresses and prompt follow-up of patients who are late for their appointments are required. LESSONS LEARNED: ART clinics in resource-poor countries should ensure that patients’ addresses are correct and comprehensive. Clinics should also undertake contact tracing as soon as possible in the event of non-attendance, consider facilitating access to ART clinics and take loss to follow-up into consideration when assessing death rates.